The Effect of Work Stress On Turnover Intention Among Employees In The Qa Department PT. X - Berliana Octaviani, Annisa; Wina Lova Riza, Wina; Pratomo, Yuwono (International Journal of Science and Environment (IJSE), 2025)
This study examines the effect of job stress on turnover intention among employees in the Quality Assurance (QA) department at PT. X. In an era of increasing globalization, high employee turnover has become a critical concern for businesses, with job stress identified as a primary catalyst. This quantitative research used a causal-comparative design, with a total sampling technique applied to all 64 employees of the QA department. Data were collected using the Indonesian versions of the six-item Turnover Intention Scale (TIS-6) and the ten-item Perceived Stress Scale (PSS-10). The data were analyzed using simple linear regression via IBM SPSS 25. The results showed a significant and positive effect of job stress on turnover intention (p=0.000<0.05), with job stress accounting for a substantial 76% (R2=0.760) of the variance in turnover intention. The findings highlight the importance of proactive stress management strategies within organizations to reduce turnover rates and improve employee retention.